Ας μην αφήσουμε την κρίση να πάει χαμένη: προς μια «Πράσινη Φορολογική Μεταρρύθμιση» - Ζαχαριάδης, Θεόδωρος (My University, 2015)
The recent economic crisis in Cyprus has given rise to many recommendations on how to stimulate the economy and increase employment, by adopting a ‘new economic model’. At the same time, the country is faced with several energy and environmental challenges – low energy productivity, the highest water scarcity problem in Europe and among the highest per capita waste generation rates in the continent2. The economic downturn of recent years has helped Cyprus meet some intermediate environmental targets, but this compliance is only temporary: as economic growth is expected to resume, it will be increasingly difficulty for the country to fulfil its international energy and environmental commitments. This policy brief attempts to demonstrate that it is possible to simultaneously address the above concerns, i.e. reconcile economic growth and job creation with environmental protection, with the aid of a ‘Green (environmentally friendly) Tax Reform’ (GTR). By definition, a GTR (also called green fiscal reform) involves a reform of the national tax system whereby there is a shift of the burden of taxes towards environmentally damaging activities such as unsustainable resource use or pollution. The proposed GTR for Cyprus will mainly comprise:  Introducing a carbon tax to apply on fuels used across all economic sectors, and increasing taxation on the use of resources (e.g. water) and other environmentally harmful activities (e.g. waste production, air pollution and use of fertilizers and pesticides); while at the same time  Decreasing labour taxation (e.g. by reducing social security contributions of both employers and employees). As Cyprus is currently running balanced public budgets, this reform can be designed so as to prove revenue-neutral: the extra revenues to be generated through environmental taxes can be roughly equal to the public revenues lost through the reduction in labour taxes. The Cypriot economy is labour-intensive, hence the reduction in labour taxation is expected to lower costs of most enterprises even despite the increase in energy costs; a few exceptions may need to be addressed in a targeted manner. Part of the additional revenues can also be used to compensate low-income households for the increase in their energy bills, or finance green investments such as energy refurbishments in buildings or improvements in public transport infrastructure. This reform can be implemented gradually over a longer period (e.g. five years) in order to provide time to firms and consumers to adapt to the new situation. At today’s quite low international crude oil prices, a carbon tax will not increase fuel prices substantially, so that rising energy costs should be manageable by all households and firms. Our proposal has multiple environmental benefits. Individuals and enterprises will gradually adjust their investment decisions and consumption behaviour in order to adapt to the new tax system, thereby reducing the use of energy in industry, buildings and motor vehicles, and substituting towards low-carbon or zero-carbon energy sources. This in turn will reduce the energy import dependency of Cyprus, and thereby improve its persistent current accounts deficit16; improve air quality by reducing the emissions of other air pollutants too; and contribute to climate change adaptation since e.g. a better insulated building is less vulnerable to high external temperatures. More than 20 years of experience in a number of EU Member states shows that a Green Tax Reform can be beneficial for the economy and employment. Traditionally, tax systems have relied on direct taxes of labour and income in order to generate public revenues. In the European Union, for example, direct taxes accounted for two thirds of total tax receipts in 2012; environmental taxes accounted for merely 6.1% of the total, and their relative contribution (as a fraction of national GDP) has been declining since 20005. This endangers employment and economic growth as it increases the cost of labour, in addition to encouraging tax avoidance and illegal labour. At the same time, as most energy-using and natural resource-depleting activities are taxed below their socially optimal levels, this constitutes a subsidy to environmentally harmful activities; such subsidies account internationally for billions of Euros each year6,7,8. A shift from labour to environmental taxation can change this picture. In several case studies around Europe it has been clearly demonstrated that energy/environmental taxes are less detrimental to employment and growth than other direct and indirect taxes9,10. If the environmental tax increases are accompanied by reductions in labour taxation, the overall effect can be beneficial in both macroeconomic and environmental terms11. Such a reform reduces distortions on economic activity and changes relative economic prices, thereby fostering innovation and encouraging investment in green economy sectors, which can create a competitive advantage for the economy. In the case of greenhouse gas emissions this reform is certainly needed: as shown in Figure 14, if economic growth rebounds, the emissions of economic sectors that are not subject to the EU Emissions Trading System (ETS) will start increasing again, and Cyprus will not be able to comply with the significant emission reduction targets for year 2030 as decided by EU leaders in October 2014. A carbon tax can decrease these emissions substantially over the medium term. In a similar fashion, taxes on other environmentally harmful activities can considerably reduce the level of environmental degradation in areas such as fertilizer and pesticide use, waste generation, and water overconsumption. Nineteen ‘Green Tax Commissions’ have been formed in European countries in recent years, with the objective to examine the potential of environmental fiscal reforms. As a result, eight countries (Denmark, Finland, France, Germany, the Netherlands, Portugal, Sweden and the United Kingdom) have adopted such reforms, while Ireland has employed partial measures in the same direction (carbon tax, plastic bag levy), and the government of Italy is also at an advanced stage of adopting similar measures. Major international organisations such as the OECD, the IMF and the World Bank have underlined that Green Tax Reforms are the most efficient way to ensure both fiscal sustainability and environmental protection12,13. The European Commission, in the frame of the ‘European Semester’ process of monitoring the macroeconomic stability of Member States, has recommended to many countries the adoption of environmentally-oriented fiscal reforms14 and has commissioned relevant studies for this purpose15. This is in line with the EU’s broader strategic initiative for a ‘resource-efficient Europe’17 achieving a ‘circular economy’18. Recently, the European Parliament’s Economic Affairs Committee has also urged European governments to shift taxes away from labour to environmentally harmful activities20, and the Council of EU Environment Ministers has emphasised that “shifting taxation from labour to pollution, energy and resource use in a budgetary neutral manner may be an appropriate tool to promote employment creation and greening the economy”21. In conclusion, the ‘new economic model’ for Cyprus that is under discussion after the recent economic crisis cannot be prescribed or defined ex ante. It will be the result of several factors including the ingenuity of individuals and enterprises, societal choices, technological improvements, and changes in the international policy landscape. A government’s role is to formulate long-term targets and provide a coherent policy environment that can enable realising these targets. In this context, this policy brief claims that it is possible to switch Cyprus to a low-carbon economy in the medium to long term, in line with the broad EU sustainability strategy, thereby promoting employment and economic growth while at the same time achieving significant environmental improvements. A Green Tax Reform is essential for this purpose. Recent experience in many European countries has shown that such a reform is economically and politically feasible, beneficial for economic growth and environmental protection, and with manageable side-effects. We therefore propose the formation of a Committee on Green Tax Reform in Cyprus that within a six-month period should prepare a concrete proposal for a revenue-neutral environmental fiscal reform, along with an assessment of its economic, environmental and social implications. Ministries of Finance and the Environment as well as professional associations from the private sector must participate in this Committee, which can also include members from other governmental departments, stakeholders from the private sector, NGOs and academia - and should preferably be chaired by an independent entity of either the public or the private sector.
Don’t let a crisis be wasted – proposal for a green tax reform in Cyprus
Keywords: Πράσινη φορολογική μεταρρύθμιση; Περιβαλλοντικές πολιτικές